Refining the trophic diversity, network structure, and bottom‐up importance of prey groups for temperate reef fishes - S. Zarco‐Perello; S. Bennett; J. Goetze; T. H. Holmes; R. D. Stuart‐Smith; E. R. White (Ecosphere)
Abstract Marine fish communities are highly diverse and contribute significantly to ecosystem processes. However, understanding their specific functional roles and the importance of different prey groups for sustaining fish communities has been limited by the historical classification of fishes into a few coarse trophic guilds. Using diet information to perform a high‐resolution trophic classification of 298 temperate reef fish species distributed across south‐western Australia, we built metacommunity and subregional trophic networks to evaluate the most important trophic relationships and energy pathways in temperate reefs. We identified 26 specialized trophic guilds within the groups of herbivores, zoobenthivores, zooplanktivores, piscivores, and cleaners. Zoobenthivorous fishes had the highest species richness and trophic diversity with 191 species in nine guilds. Consumers of crustaceans showed greater species redundancy at the metacommunity level. In contrast, a low redundancy of echinodermivores could represent a risk to local capacity for top‐down control of sea urchins across the region. Finer scale analysis of prey at the family level showed that piscivorous guilds may influence different trophic pathways, with some guilds consuming other piscivorous fishes, while others consume lower trophic levels, particularly crustaceavores. Evidence of predation on herbivorous guilds was only found for turf grazers, suggesting that fish herbivory might not function as a major direct link between primary producers and higher trophic levels. Among the prey consumed by fishes, micro‐crustaceans and decapods accounted for 33% of all diet proportions. The importance of macrophytes to the fish community likely resides indirectly through the trophic pathway of herbivorous and detritivorous invertebrates, particularly crustaceans, which are more consumed by fishes than macrophytes themselves. Comparison of trophic networks in the region showed that warmer locations had higher species redundancy per node and higher strength in trophic interactions. Yet, all networks had structural properties consistent with the meta‐network regarding the importance of prey groups and modularity. Considering high‐resolution predator–prey interactions enhances our understanding of the blue‐print of ecosystem functions in shallow marine systems. Identifying the specific trophic significance of different consumers and prey groups is important for ecological forecasting and the prioritization of conservation and resource management regulations in our current fast‐changing world.